Cannabinoid CB2 Receptors Modulate Microglia Function and Amyloid Dynamics in a Mouse Model of Alzheimer’s Disease - Ruiz de Martín Esteban, Samuel; Benito-Cuesta, Irene; Terradillos, Itziar; Martínez-Relimpio, Ana M.; Arnanz, M. Andrea; Ruiz-Pérez, Gonzalo; Korn, Claudia; Raposo, Catarina; Sarott, Roman C.; Westphal, Matthias V.; Elezgarai, Izaskun; Carreira, Erick M.; et al. (Frontiers in Pharmacology, 2022)
The distribution and roles of the cannabinoid CB2 receptor in the CNS are still a matter of debate. Recent data suggest that, in addition to its presence in microglial cells, the CB2 receptor may be also expressed at low levels, yet biologically relevant, in other cell types such as neurons. It is accepted that the expression of CB2 receptors in the CNS is low under physiological conditions and is significantly elevated in chronic neuroinflammatory states associated with neurodegenerative diseases such as Alzheimer’s disease. By using a novel mouse model (CB2EGFP/f/f), we studied the distribution of cannabinoid CB2 receptors in the 5xFAD mouse model of Alzheimer’s disease (by generating 5xFAD/CB2EGFP/f/f mice) and explored the roles of CB2 receptors in microglial function. We used a novel selective and brain penetrant CB2 receptor agonist (RO6866945) as well as mice lacking the CB2 receptor (5xFAD/CB2−/−) for these studies. We found that CB2 receptors are expressed in dystrophic neurite-associated microglia and that their modulation modifies the number and activity of microglial cells as well as the metabolism of the insoluble form of the amyloid peptide. These results support microglial CB2 receptors as potential targets for the development of amyloid-modulating therapies.